Towards an integrated health risk assessment framework of soil heavy metals pollution: Theoretical basis, conceptual model, and perspectives. (1st January 2023) - Yang, Shiyan; Sun, Lijuan; Sun, Yafei; Song, Ke; Qin, Qin; Zhu, Zhengyi; Xue, Yong
Abstract: The health risk of soil heavy metals pollution has been gaining increasing public concern. However, many countries have not set their own health risk assessment (HRA) framework and most of the existing studies directly referred to the USEPA risk assessment model and parameters. For those countries that do not propose an original HRA framework, the experience of developed countries is crucial for advancing their own HRA system. This study systematically reviewed the development of HRA framework in some representative developed countries. The theoretical basis, conceptual model, progress, and challenges of HRA researches concerning soil heavy metals pollution were summarized. By recalling and comparing the health risk-related laws and guidance in the USA, UK, and Japan, results showed that the construction of HRA framework varied between these countries, but HRA has become the main method for deriving their soil environmental criteria. We further summarized the evaluation scales, land use types, exposure pathways, and sensitive receptors of HRA studies, and highlighted the key parameters affecting health risk outputs. There has been a shift toward the incorporation of probabilistic modeling, metals bioavailability, and sources emission characteristics into recent HRA studies. Nonetheless, challenges remained on how to minimize the uncertainty of generating probability distribution and detecting metal bioavailability. To facilitate the development of HRA framework, it was advised that developing countries should strengthen the theoretical researches of health risk and localization researches of exposure factors. Future directions are suggested to tend to: 1) promote sensitive analysis to quantify the impact of distribution assumptions on health risk outputs, 2) derive reasonable risk threshold and consistent evaluation protocol for bioavailability-based health risk assessment method, and 3) strive to explore the combined health effect of exposure to heavy metals in soil through source-media-receptor integrated studies. Graphical abstract: Image 1 Highlights: Health risk assessment (HRA) is the main method for deriving soil threshold. Land use type determines exposure pathways and sensitive receptors in HRA practices. Uncertainty in probability distribution and metal bioavailability affected HRA development. Refinement and census of local exposure data is important to promote HRA system. Integrated HRA analysis from source to receptor is needed to reduce exposure risk.